2015
DOI: 10.1080/15299732.2014.969468
|View full text |Cite
|
Sign up to set email alerts
|

Healing Pathways: Longitudinal Effects of Religious Coping and Social Support on PTSD Symptoms in African American Sexual Assault Survivors

Abstract: African American women are at slightly increased risk for sexual assault (Abbey, Jacques-Tiaura, & Parkhill, 2010). However, due to stigma, experiences of racism, and historical oppression, African American women are less likely to seek help from formal agencies when compared to White women (Ullman & Filipas, 2001; Lewis, Resnick, Smith, Best, & Saunders, 2005) and/or women of other ethnic backgrounds (Ahrens, Abeling, Ahmad, & Himman, 2010). Therefore, the provision of culturally appropriate services, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…Some of the studies focusing on general religious coping (without differentiating between positive and negative coping) showed positive associations between this variable and good psychological functioning: Currier et al ()—positive association with PTG and negative with distress; Hawthorne, Youngblut, and Brooten ()—negative associations with grief, depression, PTSD (only in women), and positive with PTG (only in women); Maschi, Viola, and Morgen ()—positive link with global mental health; Saxon et al (), and negative links with mental disorders (only in women). Nevertheless, no significant links with symptoms of PTSD were demonstrated in a longitudinal study (Bryant‐Davis et al, ; all participants were women); prayer as coping was not linked with symptoms of depression in Ai et al (). Positive links between religious coping and mental disorders were found in Adofoli and Ullman () and Bryant‐Davis, Ullman, Tsong, and Gobin ().…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Some of the studies focusing on general religious coping (without differentiating between positive and negative coping) showed positive associations between this variable and good psychological functioning: Currier et al ()—positive association with PTG and negative with distress; Hawthorne, Youngblut, and Brooten ()—negative associations with grief, depression, PTSD (only in women), and positive with PTG (only in women); Maschi, Viola, and Morgen ()—positive link with global mental health; Saxon et al (), and negative links with mental disorders (only in women). Nevertheless, no significant links with symptoms of PTSD were demonstrated in a longitudinal study (Bryant‐Davis et al, ; all participants were women); prayer as coping was not linked with symptoms of depression in Ai et al (). Positive links between religious coping and mental disorders were found in Adofoli and Ullman () and Bryant‐Davis, Ullman, Tsong, and Gobin ().…”
Section: Resultsmentioning
confidence: 93%
“…Some longitudinal studies showed the buffering role of adaptive religious constructs on mental health (or religious struggle on the greater severity of symptoms). The only exception was Bryant‐Davis et al (), who found no significant links in a sample of female survivors of sexual trauma. To a certain extent, papers that assess general religious affiliation (especially if the assessment is conducted not long after the event) can also provide some information about potential causality, as this variable is less volatile in time than other religiosity measures.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the prevalence of PTSD was 35.7% among the surviving children in the Municipality of Peristeri six to seven months after the 1999 Athens earthquake [8]. Variations in the prevalence of PTSD have been noted and attributed to differences in study measurements and assessing times, as well as different age, race and cultural background of the samples [8][9][10].…”
Section: Introductionmentioning
confidence: 92%
“…To date, studies on church attendance have produced the most robust evidence, with several prospective studies demonstrating a significant protective effect of church attendance on mortality and depression (13)(14)(15)(16)(17). Self-assessed spirituality and religious coping have also been found to have a significant prospective associations with hypertension (18,19), colon cancer (20), HIV outcomes (21), cognitive functioning and mental health (22)(23)(24)(25)(26)(27)(28)(29), change in pulmonary function among adolescents with cystic fibrosis (30,31), and CD4 levels and viral load among HIV/AIDS patients (32)(33)(34).…”
mentioning
confidence: 99%